Key facts from a traditional Colombian food market: Galería El Porvenir - Reep, Alexandra; Polo Sierra, Carolina (Bioversity International and the International Center for Tropical Agriculture, 2022)
Traditional Colombian food markets, the “Galerías”, are major players in the city’s food environment. The affordability, accessibility, convenience of preparation, and desirability of ingredients in the Galerías all play a significant role in determining peoples' food choices, diets, and consequently nutrition and health. This is the case of Galería El Porvenir in Cali, Colombia. The food flow and profiles of the average consumer and vendor are shown in these research outputs.